The Influence of Corporate Social Responsibility on Tax Avoidance among Manufacturing Companies Listed on the Indonesia Stock Exchange for the Period 2020–2023 - Tiara Shava Tasya Ol Kau (Advances in Taxation Research, 2026)
Purpose: This study aims to examine the effect of Corporate Social Responsibility (CSR) disclosure on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2020–2023. This study is grounded in stakeholder theory and legitimacy theory, which suggest that CSR disclosure reflects corporate responsibility and may influence tax-related behavior. Research Method: This study used a quantitative approach, drawing on secondary data from the annual and sustainability reports of 45 manufacturing companies, yielding 180 firm-year observations selected through purposive sampling. CSR disclosure was measured using the CSR Index (CSRI) based on GRI Standards, while tax avoidance was proxied by the Effective Tax Rate (ETR). The hypothesis was tested using a panel data regression with the Fixed-Effects Model. Results and Discussion: The findings show that CSR disclosure has a significant negative effect on tax avoidance. Companies with higher CSR disclosure tend to have higher ETR values, indicating lower tax avoidance. This result suggests that CSR disclosure is associated with stronger tax compliance and supports stakeholder and legitimacy theories in explaining corporate tax practices. Implications: This study provides practical implications for regulators, investors, and stakeholders by showing that CSR disclosure may signal corporate tax behavior. It also encourages companies to strengthen CSR as part of responsible corporate governance. Originality: This study provides empirical evidence on the relationship between CSR disclosure and tax avoidance in Indonesian manufacturing companies during the post-pandemic period.